PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK, DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN PADA CV. SURYA BAROKAH MANDIRI BANYUWANGI - Amelya, Risma; Izzudin, Ahmad; Nursaidah, Nursaidah (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
This research aims to determine the influence of service quality, product quality and trust on customer loyalty at CV. Surya Barokah Mandiri Banyuwangi. The type of research used was quantitative research and data collection techniques used observation, interviews and questionnaires for 136 respondents using purposive sampling techniques. The analytical tools used in this research are validity test, reliability test, classical assumption test, multiple linear regression analysis, T test, and simultaneous R2 test and F test. The results of testing the first hypothesis (H1) show that the service quality variable is 0.173, which is greater than 0.05, which means that the service quality variable has no influence on customer loyalty. The results of testing the second hypothesis (H2) show that the product quality variable is 0.610, where this value is greater than 0.05, so it can be concluded that the product quality variable has no influence on customer loyalty. The results of testing the third hypothesis (H3) show that the trust variable is 0.00 where the value is smaller than 0.05, so it can be concluded that the trust variable has a variable on customer loyalty.